Variasi Substitusi Rumput Laut Terhadap Kadar Serat Dan Mutu Organoleptik Cake Rumput Laut (Eucheuma cottonii) - Handayani, Ratih; Aminah, Siti; Suyanto, Agus (Jurnal Pangan dan Gizi, 2011)
Seaweed can be applied as an added ingredient in cake because that is contains a dietary the fiber. Cake is baked with the dough ingredients flour, sugar, eggs and margarine. Research Design with the independent variables substitution seaweed 0%, 10%, 20%, 30%, and the dependent variable dietary fiber and organoleptic value with 5 replications. There is a significant effect on the added of seaweed on dietary fiber at the cake, whereas not significant on organoleptic value. The dietary fiber highest at 30% substitution (4.05%) and the lowest at 0% substitution (2.27%). Cake seaweed most preferred is 30% with an average assessment score highest at 3.8 (like). The most preferred organoleptic value from seaweed cake is brownish yellow, fragrant, soft texture and sweet taste.